Cultural Meaning in Jambi Batik Motifs through Peirce's Semiotic Perspective - Gunawan Wiradharma; Rahmat Alifin Valentino; Gustiana Sabarina; Miftahunnisa' Igiriza; Salaisyah Amalia Yusuf (EKSPRESI DAN PERSEPSI : JURNAL ILMU KOMUNIKASI, 2026)
Jambi batik is not just a traditional cloth, but a cultural artifact that encapsulates the philosophical, ecological, and spiritual values of the Jambi Malay community. Despite its high cultural richness, most existing studies emphasize the visual and historical aspects. This study aims to explore the meaning contained in Jambi batik motifs using Charles Sanders Peirce’s semiotic approach. The method used is descriptive qualitative research with data collection techniques through direct observation at the Jambi Siginjei Museum and Azmiah Batik House, and in-depth interviews with museum curators and batik makers. The results of the study show that the objects owned by Jambi batik motifs include natural elements such as plants, animals, history, and forms of objects that are close to the lives of the Jambi people. Representamens appear as ornaments or visual motifs such as the Durian Pecah motif, The Tempuk Maggis motif, The Kaco Piring motif, and others, which contain symbolic values. The community understands that the interpretations emerging from the meaning-making process function as religious symbols, markers of social status, and representations of life philosophies. This study concludes that Jambi batik is not only a visual artifact but also a cultural text that contains a complex sign system. These findings can provide theoretical contributions to the development of cultural semiotic studies and practical contributions in preserving batik as an intangible heritage that represents indigenous knowledge and identity.